STUDY ON THE PROCESSING AND PRESERVATION OF JACKFRUIT BISCUITS - T.UMA MAHESWARI*, M. RAJKUMAR and VIDHU VALSAN, (The Journal of Research ANGRAU, 2019)
The study on processing of jackfruit biscuit was carried out during the year 2018 in a CompletelyRandomized Design with four formulations (33%, 31%, 29% and 27% of wheat flour concentrations for 500g ofjackfruit pulp). The effect of processing on the nutritional quality, sensory quality, shelf life and cost economicswere calculated. The formulation,T3 ( Jackfruit with 29% of wheat flour) was evaluated as the best treatmentwhen compared to other formulations with moisture content of 12.87%, fat content of 2.87g and a proteincontent of 5.87g in 100g portion of the biscuits. The formulation T3 was found to have a maximum shelf lifeperiod of five months. The average sensory scores for taste (8.6), colour (8.4), flavour (8.4) and overall acceptability(8.5) of jackfruit biscuits were initially maximum in the same treatment. Cost of production of one kg of thebiscuits was Rs.72 with a benefit-cost ratio of 1.62.